A conservation perspective on the mechanisms that influence plant-pollinator interactions - Biella, Paolo (Jihočeská univerzita, 2019)
Several aspects of plant-pollinator interactions are presented in the thesis. It contains a review on the open questions of plant-pollinator interactions from single species to complex networks. The following sections document novel results. Firstly, the conservation of complex pollination networks is addressed through the hierarchy of species' importance. In addition, the habitat requirements and interactions of a threatened rare pollinator species are explored. In the following chapters, the results from manipulative approaches applied in the field to plant-pollinator interactions are presented. The effect of pollinator's population decline on pollinators' foraging for pollen is investigated. Moreover, the way plant species loss impact several aspects of pollinator visitation is presented. Lastly, the impact of species removal on plant-pollinator network topology and on species ability of establishing new interactions is investigated.
A conservation perspective on the mechanisms that influence plant-pollinator interactions
Keywords: Plant-pollinator networks; pollinator decline; mutualisms; pollination service; species distribution models; rarity; interactions; resource use.